The role of the cash flow statement to provide accounting information for the financial decision-making process: (Case study International Islamic Bank of Kurdistan in the year 2018) - Hakar Abubakir bayz; Diary Jalal Ali; Hawkar Anwer Hamad (QALAAI ZANIST JOURNAL, 2021)
This study aims to know the role of the cash flow statement in providing accounting information for the financial decision-making process in order to provide information on historical changes in cash for the institution by using cash flows that classify operation, investment, and financing flows. In this research, we rely on the real data in the International Islamic Bank of Kurdistan in the year 2018 to reach concise results in the financial statements and the effect of decision-making to progress in this financial bank. The study results indicated that: 1- By preparing a list of cash flows, the unit can get an accurate view of its operating, financing, and investment operations. 2- That within the list of flows there is information on the aspects of receipts and cash payments, and this is useful for knowing the financial position of the economic unit